Sistem pengendalian manajemen berbasis nilai publik: Studi kasus pada Suroboyo Bus - Enrica Celia; Fidelis Arastyo Andono (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2023)
The objective of this paper is to deeply study about how the management control system of a public sector organisation contributes to the creation of public value as expected by the stakeholders. This research is designed as a qualitative case study with the interpretive paradigm. Suroboyo Bus case was chosen as it fits with the purpose of the study and its accessibility. Public Value Management (PVM) theory explains the investigated phenomenon, with the levers of control framework used as the theoretical reference to explain the MCS of Suroboyo Bus. This research found that the MCS of Suroboyo Bus was designed to support the creation of public value. The internalised value of the Suroboyo Bus managers and staff have made the MCS implementation focus upon the public values. The change from UPTD to BLUD became the foundation to facilitate the public value creation. The MCS in operational, budgetary and administration cycles are focused upon maintaining and improving the service quality of the mass public transport of Suroboyo Bus. However, this result may differ across organisational context, hence it is necessary to further advance the study to other public organisations to enhance the knowledge of MCS and public value creation.